An exploratory study of the Directorate of Customs and Excise’s perceptions about the performance management system of the public service in Namibia - Anghuwo, Jacobina Taukondjele (Stellenbosch : Stellenbosch University, 2018)
Thesis (MPA)--Stellenbosch University, 2018.